Measurement of drug-abuse inmates’ prison climate: Confirmatory factor analysis - Mahadzirah, Mohamad; Norhilmi, Muhammad; Nor Azman, Mat Ali @ Salim (Serials Publications Pvt. Ltd., 2017)
Correctional or rehabilitation programmes have better effects on offenders in prisons that have a positive social climate. Different aspects of prison environment may have different impacts on different groups of inmates. This study was carried out to identify the underlying factors manifesting prison climates to gain humanitarian insights in designing and executing effective rehabilitation programmes among drug-abuse inmates. Data were collected using self- administered questionnaires. A total of 376 drug-abuse inmates were involved in this study. The respondents were selected using a two-step sampling technique. An area sampling technique was performed followed by a simple random sampling. Findings of this study, using a confirmatory factor analysis, supplement the literature examining the underlying specific factors manifesting the latent constructs of prison climate. The study suggested that Reintegration, Activities, and Right and rules were aspects of drug-abuse prison climate which require emphasis to enhance the effectiveness of prison rehabilitation programmes.